1994
DOI: 10.1177/172460089400900406
|View full text |Cite
|
Sign up to set email alerts
|

Total Sialic Acid as a Tumor Marker for Oral Cancer

Abstract: Serum sialic acid levels were measured in 80 healthy subjects, in 60 patients with benign tumors and in 110 patients with oral cancer. It was shown that these levels were significantly elevated in oral cancer patients compared to healthy controls and patients with benign tumors (p < 0.01); they were higher in patients with stage III and stage IV disease than in those with stage I and II disease (p < 0.01). However, no difference was observed between healthy controls and stage I and II cancer patients. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This suggested that malignant transformation brings changes in cell surface glycoconjugates, which is in accordance with earlier reports (10). Elevations in the levels of sialic acid appeared to reflect tumour burden and correlated well with the stage of the primary lesion and presence of distant metastasis (4, 10, 17, 21). We also observed significant progressive elevations in serum TSA and LSA values in oral cancer with stage of the malignant disease.…”
Section: Discussionmentioning
confidence: 98%
“…This suggested that malignant transformation brings changes in cell surface glycoconjugates, which is in accordance with earlier reports (10). Elevations in the levels of sialic acid appeared to reflect tumour burden and correlated well with the stage of the primary lesion and presence of distant metastasis (4, 10, 17, 21). We also observed significant progressive elevations in serum TSA and LSA values in oral cancer with stage of the malignant disease.…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, no reliable circulating tumor marker currently is available for use in the treatment of patients with oral SCC, despite efforts to establish such a marker 26–30, 37. This is a major drawback in the field because the importance of the early detection of these lesions cannot be overemphasized.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor markers, which have been accepted as a valuable tool for diagnosis, prognosis, and treatment monitoring in recent years,12–18 could be an easy and desirable means of achieving this purpose. Various tumor markers have been examined for their value in detecting head and neck and/or oral carcinoma 19–31. However, the main drawback of these markers was their low sensitivity for head and neck carcinoma, which rendered them useless for clinical purposes.…”
mentioning
confidence: 99%
“…Increased levels of serum TSA and/or LSA have been observed in various patient groups suffering from advanced ovarian carcinoma [52], brain tumours [53][54][55], leukaemia [56], lung cancer [57], cervical cancer [58], carcinoma of the hypopharynx and larynx [59], rectal, large intestinal and bronchogenic cancers [60], malign pleural effusion [61], oral cancer [62], melanoma [63], stomach, breast [64], colorectal, gall bladder cancer [65], thyroid and Hodgkin's cancers [55], sarcoma [52], and endometrial cancer [66]. For levels of TSA, LSA, TSA/total protein and protein-bound SA in sera from cancer patients and their control subjects (see Table 4).…”
Section: Sa Concentrations In Malignanciesmentioning
confidence: 99%
“…The increase in SA has been observed to correlate positively with tumour burden [55,58,62,63,65,67,68], i.e. the level of metastasis.…”
Section: Sa Concentrations In Malignanciesmentioning
confidence: 99%